1991
DOI: 10.1246/cl.1991.185
|View full text |Cite
|
Sign up to set email alerts
|

Novel Carboxymethylation of Styrene Derivatives by Mn3+-Mediated Electrooxidation

Abstract: Anodic oxidation in a mixed solvent of acetic acid and acetic anhydride containing a variety of styrene derivatives, small amounts of Mn(OAc)2·4H2O and Cu(OAc)2·H2O brought about a facile carboxymethylation to give the corresponding γ-butyrolactones as the main products in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Mn(OAc) 3 ·2H 2 O is not particularly expensive on a laboratory scale, but its use on an industrial scale may be problematic. Several groups have demonstrated that Mn(III) can be used in catalytic quantities and regenerated electrochemically in situ . ,,, In some cases, good yields of products are obtained with only 0.2 equiv (10%) of Mn(III) or Mn(II). In other cases the electrochemically mediated reactions proceed in substantially lower yield or give different products.…”
Section: Oxidants1 Mn(iii)mentioning
confidence: 99%
“…Mn(OAc) 3 ·2H 2 O is not particularly expensive on a laboratory scale, but its use on an industrial scale may be problematic. Several groups have demonstrated that Mn(III) can be used in catalytic quantities and regenerated electrochemically in situ . ,,, In some cases, good yields of products are obtained with only 0.2 equiv (10%) of Mn(III) or Mn(II). In other cases the electrochemically mediated reactions proceed in substantially lower yield or give different products.…”
Section: Oxidants1 Mn(iii)mentioning
confidence: 99%
“…Addition products from 6b and diethyl 2-bromo-2-methylmalonate (21) [10,11] or dimethyl 2-bromo-3-ethylsuccinate 23 [13] were formed in 87 and 50%, respectively (scheme 5).…”
Section: Comentioning
confidence: 99%
“…Using the Mn(OAc) 2 ±Cu(OAc) 2 mediator system, g-lactones have been obtained in acceptable yields from acetic acid and styrenes, 246,250 and alk-2-enyl-and cycloalk-2-enyl-substituted cyanoacetic esters were synthesised from ethyl cyanoacetate, alkenes and cycloalkenes. 246,247 In these reactions the carboxymethyl and (ethoxycarbonyl)cyanomethyl radicals together with their adducts with alkenes are formed as intermediates; the former species result from single-electron oxidation of acetic acid and ethyl cyanoacetate by electrogenerated Mn(OAc) 3 and the latter arise upon the addition of the primary radicals to alkenes.…”
Section: A Reactions Induced By Electrooxidation Of Manganese Compoundsmentioning
confidence: 99%